Dilemmata der Nachhaltigkeit: Zur Relevanz und kritischen Reflexion in der Nachhaltigkeitsforschung Ein Leitfaden - Henkel, Anna; Berg, Sophie; Mader, Dimitri; Müller, Ann-Kristin; Bergmann, Matthias; Gruber, Holli; Siebenhüner, Bernd; Speck, Karsten (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The concept of sustainability is increasingly losing its contours. This study reflects on the understanding of sustainability used in research and science. Its authors thus enable us to concisely determine not only concrete contributions to sustainability, but also its limits. Based on an analytical understanding of sustainability and the basic structure of practical dilemmas, the book identifies typical conflicts as causes of dilemmas. Meta-criteria of sustainability allow us to identify dilemmas and to clarify and deal with them practically at an early stage. Finally, the study applies these meta-criteria in concrete project contexts by means of guiding questions for reflection.